Penilaian Komponen Hasil dan Indeks Intercropping 22 Jagung Hibrida Pada Sistem Intercropping Jagung-Kedelai - Jajang Supriatna; Muhamad Sahrul Sidik; Rama Adi Pratama; Fakhri Nasharul Syihab; Yuyun Yuwariah; Dedi Ruswandi (Paspalum: Jurnal Ilmiah Pertanian, 2023)
This study aims to determine the performance of the yield components and the intercropping index of 22 hybrid maize in the maize-soybean intercropping system. This research was carried out in Cikajang, Garut Regency from January 2021 to June 2021. The method used in this research is a quantitative descriptive and experimental method. The experimental design used was a randomized block design with 27 treatments made in 3 replications. The genetic material used was 22 test hybrids from the Padjadjaran University collection and 5 commercial hybrids as comparisons. Assessment of yield components was carried out using The Least Significant Increase (LSI) test assessed for 4 yield components consisting of cob diameter, cob length, number of seeds cobs, and dry seed/plant weight. Intercropping index assessment was analyzed based on the calculation of Land Equivalent Ratio (LER), Area Time Equivalent Ratio (ATER), and Aggressivity (A). The results showed that there were 4 hybrids that had high yields in the maize-soybean intercropping system including DRc6 x DRc7, DRc8 X MDRc18.8.1, DRc8 X MDRc1.1.3 and MDRc3.1.4 X MDRc18.5.1. There are 3 profitable hybrids in the intercropping system of soybean maize based on the intercropping index including DRc4 X MDRc7.2.3, DRc8 x DRc9, and MDRc7.4.3 x MDRc18.8.1.